A video production thesis on abandonment of children in hospitals (MARCH 2007) - Casimillo, Princess L.; Coderes, Katrina April V.; Quinto, Jacqueline Ann R. and Tabunda, Jenna R. 4 0 16; 5 (2007)
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2007.;Bachelor of Science in Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2